Modified guanidine ionic liquid / mesoporous carbon composite fiber material applied to CO2 capture and preparation method thereof

By designing modified guanidine ionic liquid and mesoporous carbon composite fiber materials, the problems of poor adsorption capacity and increased material viscosity at low CO2 concentration are solved, and efficient and stable CO2 capture and cost reduction are achieved.

CN119680346APending Publication Date: 2025-03-25TIANFU NEW ENERGY RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411977367.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art has poor adsorption capacity of ionic liquids at low industrial exhaust CO2 concentration, and the accumulation of CO2 adsorption products leads to an increase in material viscosity, hindering heat mass transfer and reducing the liquid film mass transfer coefficient.

Method used

Modified guanidine-based ionic liquid/mesporous carbon composite fiber material is used to improve CO2 adsorption capacity and mass transfer performance through the modification of long alkyl chain quaternary amine functional groups and highly polar amino acid groups, and achieve efficient CO2 physical adsorption through the high specific surface area and pore structure of mesporous carbon materials.

Benefits of technology

It realizes efficient capture of industrial exhaust CO2, reduces the problem of increasing viscosity of adsorbent, improves the thermal stability and circulation of materials, and reduces the cost of removing industrial exhaust CO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680346A_ABST
    Figure CN119680346A_ABST
Patent Text Reader

Abstract

The invention discloses a modified guanidine ionic liquid / mesoporous carbon composite fiber material applied to CO2 capture and a preparation method of the modified guanidine ionic liquid / mesoporous carbon composite fiber material. The composite fiber material mainly comprises a mesoporous carbon material modified by hexadecyl trimethyl ammonium bromide, guanidine ionic liquid modified by 1-bromohexane-piperidine and lysine, and a CO2 adsorbent layer formed by a polyacrylic acid (PAA) material. The guanidine ionic liquid is modified by a long alkyl chain quaternary amine functional group and a high-polarity amino acid group, so that the chemical adsorption capacity is improved; then introducing the long alkyl modified mesoporous carbon carrier into the modified ionic liquid to enhance the physical adsorption capacity; finally, a modified guanidine ionic liquid / mesoporous carbon composite fiber CO2 adsorbent layer is prepared through electrostatic spinning, the gas transmission and adsorption capacity is further improved, the problem that the CO2 adsorption capacity of ionic liquid is low is solved, and efficient capture of CO2 in industrial exhaust gas is improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to the technical field of carbon dioxide adsorption, and in particular to a modified guanidine ionic liquid / mesoporous carbon composite fiber material used for CO2 capture and a preparation method thereof. Background Art

[0002] Flue gas produced by the combustion of fossil fuels is the main source of carbon dioxide (CO2) in the atmosphere. Its large-scale emission causes environmental problems such as sea level rise, global warming, and polar ice melting. At present, the capture of CO2 in industrial exhaust gas is mainly based on the alcohol amine method. This process uses the selective chemical absorption of CO2 by alcohol amine solution to generate carbamate or bicarbonate to achieve CO2 removal. The rich liquid after decarbonization is heated and gas stripped to achieve the recycling of decarbonized liquid and the separation of CO2. Alkylamine absorbents have the advantages of low absorption viscosity, high CO2 absorption, and low operating costs. However, from the perspective of long-term operation of industrial equipment, alcohol amine absorbents have problems such as easy volatility, oxidation, and salt formation at high temperatures, which will cause a series of problems such as large solvent loss, large amount of absorbent entrained in the captured gas, and large environmental pollution. At the same time, the existence of chemical bonds between CO2 and alcohol amine solution leads to extremely high regeneration energy consumption, which greatly reduces the economic efficiency of the CO2 removal process.

[0003] Ionic liquids (ILs) have been widely used in CO2 capture as a green solvent with low vapor pressure, stable chemical properties, small heat capacity and adjustable structure. Due to their unique characteristics and molecular structure, ionic liquids (ILs) have good stability, ultra-low volatility, designability and high CO2 solubility / selectivity, and have shown good performance in CO2 capture and separation. In particular, the non-volatility and structural adjustability of ILs make efficient and energy-saving CO2 desorption processes feasible. However, due to the low physical adsorption capacity of ILs for CO2, especially for post-combustion flue gas or even direct air capture with low CO2 concentrations, they are still unable to compete with currently available commercial solvents (such as amines and inorganic bases). In addition, the accumulation of CO2 adsorption products will lead to an increase in the viscosity of the adsorbed material, which hinders heat and mass transfer and reduces the liquid film mass transfer coefficient and heat exchange coefficient, ultimately increasing the energy consumption of industrial transportation.

[0004] Therefore, it is urgent to design and synthesize a new ionic liquid material with high CO2 absorption capacity and good thermal stability to improve the efficient capture of CO2 in industrial emission gases. Summary of the invention

[0005] The purpose of the present invention is to provide a modified guanidine ionic liquid / mesoporous carbon composite fiber material and a preparation method for CO2 capture, by synthesizing a guanidine ionic liquid / mesoporous carbon composite fiber material with high CO2 absorption capacity and good thermal stability to solve the problem of poor adsorption capacity of ionic liquids under low industrial exhaust CO2 concentration.

[0006] The first aspect of the present invention provides a modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture, wherein the composite fiber material mainly includes hexadecyltrimethylammonium bromide mesoporous carbon material, guanidine ionic liquid modified with 1-bromohexane-piperidine and lysine, and polyacrylic acid (PAA) spinning material.

[0007] Preferably, the specific surface area of ​​the mesoporous carbon in the present invention is 800-1500m 2 / g, pore size 4-8nm, pores are through holes.

[0008] By screening carbon materials with different pore structures, carbon materials with high specific surface area and high porosity can be obtained, which can achieve higher physical adsorption capacity of CO2 gas. Although mesoporous materials have a large specific surface area and provide a large number of adsorption sites, they exhibit excellent performance in adsorbing gas, liquid or solid molecules. However, their structure is usually fragile. Therefore, when screening mesoporous materials, their mechanical strength and stability need to be considered to ensure their reliability in practical applications.

[0009] Preferably, in the present invention, the specific surface area of ​​the mesoporous carbon is 1200 m 2 / g, pore size is 4nm, and the pores are through holes.

[0010] Preferably, in the present invention, the material used to modify the mesoporous carbon is a long-chain alkyl molecule such as hexadecyltrimethylammonium bromide.

[0011] By choosing hexadecyltrimethylammonium bromide, the long-chain alkyl molecules can avoid, to a certain extent, the problem of decreased physical adsorption efficiency of the porous carbon carrier due to the coverage of the ionic liquid on the surface of the carbon carrier through the steric hindrance effect.

[0012] Preferably, in the present invention, the mass ratio of hexadecyltrimethylammonium bromide to the mesoporous carbon material is 1-10% by mass.

[0013] By selecting the above range, a steric hindrance effect layer can be formed by forming long-chain molecules on the surface of the mesoporous carbon material, and the physical adsorption efficiency of the porous carbon carrier can be prevented from decreasing due to the long-chain molecules occupying too much surface and pores on the carbon carrier surface.

[0014] Preferably, in the present invention, 1-bromohexane-1-piperidine is selected for guanidine ionic liquid cation modification, wherein the guanidine ionic liquid is 1,1,3,3-tetramethylguanidine, and the material structure of the modified guanidine ionic liquid is as follows:

[0015]

[0016] After the guanidine ionic liquid cation is modified by a long alkyl chain quaternary amine functional group, the adsorption of CO2 can be improved from two aspects: steric hindrance and amine functional group: on the one hand, the quaternary amine functional group can react chemically with CO2 to form compounds such as carbamate or ammonium bicarbonate, which can increase the solubility of CO2 in the ionic liquid and improve the absorption capacity of CO2. On the other hand, the unique structure of the steric hindrance of the long-chain quaternary amine functional group can be used to improve the mass transfer performance of CO2, form a tiny interface between the liquid phase and the gas phase, and promote the rapid transmission of CO2. In addition, the reaction between the quaternized ionic liquid and CO2 is usually reversible. Under appropriate conditions, the absorbed CO2 can be released to achieve the regeneration and recycling of the quaternized ionic liquid.

[0017] Preferably, in the present invention, lysine is selected for guanidine ionic liquid to modify the anion of the guanidine ionic liquid, and the material structure of the modified guanidine ionic liquid is as follows:

[0018]

[0019] After the anion of guanidine ionic liquid is functionalized by highly polar amino acids, the amino and carboxyl groups in the amino acids can react with CO2 to form carbamates or bicarbonates, which increases the solubility of CO2 in the ionic liquid and thus improves the adsorption capacity of CO2. In addition, the adsorption between amino acid ionic liquids and CO2 is usually reversible, which can achieve the regeneration and recycling of amino acid ionic liquids.

[0020] Preferably, in the present invention, calculated by mass, the mass ratios of modified guanidine ionic liquid: modified mesoporous carbon: polyacrylic acid (PAA) in the modified guanidine ionic liquid / mesoporous carbon composite fiber material are 100-50: 40-20: 10-5 respectively.

[0021] By controlling the ratio of modified guanidine ionic liquid, modified mesoporous carbon and polyacrylic acid (PAA) in the modified guanidine ionic liquid / mesoporous carbon composite fiber material, good spinning characteristics can be ensured, a uniform and fine spinning layer can be formed, and high efficiency of CO2 adsorption can be achieved.

[0022] Preferably, in the present invention, the fiber diameter of the modified guanidine ionic liquid / mesoporous carbon composite fiber material is 200-500 nm, calculated by mass.

[0023] The second aspect of the present invention provides a method for preparing a modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture, comprising the following steps:

[0024] S1. Dissolve cetyltrimethylammonium bromide (CTAB) in an organic solvent to form a stable mixed solution. TMThe mesoporous carbon was added to the mixed solution and mechanically stirred for 24 hours. After the reaction was completed, the excess reaction product was ultrasonically washed away with anhydrous ethanol and ultrapure water, filtered with a PTFE filter membrane, and the filtered mesoporous carbon was vacuum dried at 60°C for 24 hours to obtain the modified mesoporous carbon.

[0025] S2, dissolving 1-methylpiperidine in ethyl acetate to prepare a solution; then dissolving 1,6-dibromohexane in ethyl acetate to prepare a solution. Then drip the bromohexane solution dropwise into the 1-methylpiperidine solution, react at 40°C-60°C for 24 hours, and then filter to obtain a white solid, wash the white solid repeatedly with ethyl acetate for 3 times, and then vacuum dry at 80°C for 24 hours to form an intermediate product 1-bromohexane-1-piperidine, wherein the volume ratio of 1-methylpiperidine to 1,6-dibromohexane is 1:2-5.

[0026] S3. Add 1,1,3,3-tetramethylguanidine, 1-bromohexane-1-piperidine and anhydrous potassium carbonate to acetonitrile, reflux and stir at 60°C for 24 hours, wherein the molar ratio of 1,1,3,3-tetramethylguanidine to 1-bromohexane-1-piperidine is 1:2-3. Cool and filter, add H2O to the filtrate, wash with petroleum ether, and then extract the petroleum ether phase with water. The two aqueous phases are combined, and then the above solution is extracted with dichloromethane several times, anhydrous sodium sulfate is added to remove water, and dichloromethane is removed by rotary evaporation to obtain a guanidine ion intermediate.

[0027] S4, dissolving lysine in water, adding the guanidine ion intermediate under vigorous stirring, wherein the molar ratio of lysine to the guanidine ion intermediate is 1:1-2. Then, after mixing and stirring at room temperature for 48 hours, the mixture is evaporated under reduced pressure at 55° C. Finally, vacuum drying is performed at 55° C. for 48 hours to constant weight, thereby obtaining the prepared ionic liquid—amino tetramethylguanidine.

[0028] S5, add CTAB modified mesoporous carbon to the solvent (isopropanol, ultrapure water), then add polyacrylic acid (PAA) spinning solution, after high-speed homogenization, add amino tetramethylguanidine ionic liquid to form a mixed spinning solution. Then, add it to the electrospinning device for electrospinning to obtain a modified guanidine ionic liquid / mesoporous carbon composite fiber material. Wherein, the electrospinning conditions are: static voltage of 10-40kV, injection pump flow rate of 1-4mL / h, and the distance between the spinneret and the receiving screen is 15cm.

[0029] Preferably, in the present invention, in S2, the volume ratio of 1-methylpiperidine to 1,6-dibromohexane is 1:2-5.

[0030] Preferably, in the present invention, in S3, the molar ratio of 1,1,3,3-tetramethylguanidine to 1-bromohexane-piperidine is 1:2-4.

[0031] Preferably, in the present invention, in S4, the molar ratio of lysine to the guanidine ion intermediate is 1:1-2. Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0032] The modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture provided by the present invention uses the modified composite fiber material as the CO2 adsorbent layer, which can achieve multi-dimensional improvement in CO2 capture of industrial tail gas:

[0033] (1) After the guanidine ionic liquid cation is modified by a long alkyl chain quaternary amine functional group, the adsorption of CO2 can be improved from two aspects: steric hindrance and amine functional group. On the one hand, the quaternary amine functional group can react chemically with CO2 to form compounds such as carbamate or ammonium bicarbonate, which can increase the solubility of CO2 in the ionic liquid and improve the absorption capacity of CO2. On the other hand, the unique structure of the steric hindrance of the long chain quaternary amine functional group can be used to improve the mass transfer performance of CO2, form a tiny interface between the liquid phase and the gas phase, and promote the rapid transmission of CO2. In addition, the reaction between the quaternized ionic liquid and CO2 is usually reversible. Under appropriate conditions, the absorbed CO2 can be released to achieve the regeneration and recycling of the quaternized ionic liquid.

[0034] (2) After the guanidine ionic liquid anions are functionalized with highly polar amino acid groups, the amino and carboxyl groups in the amino acids can react with CO2 to form carbamates or bicarbonates, which increases the solubility of CO2 in the ionic liquid and thus improves the adsorption capacity of CO2. On the other hand, highly polar amino acid ionic liquids enhance the adsorption of CO2. In addition, the adsorption between amino acid ionic liquids and CO2 is usually reversible, which can achieve the regeneration and recycling of amino acid ionic liquids.

[0035] (3) By introducing long alkyl-modified mesoporous carbon carriers into ionic liquids, on the one hand, the mesoporous carbon materials can be used to achieve high-efficiency physical adsorption of CO2 due to their high specific surface area, high physicochemical stability, large pore size and through-pore structure characteristics; on the other hand, the steric hindrance effect of the carbon carrier modified with long-chain alkylamines can be used to avoid the adsorption sites being occupied by ionic liquids, thereby improving the rapid transmission and adsorption of CO2.

[0036] (4) By preparing the modified guanidine ionic liquid / mesoporous carbon composite material into a fiber material, the problem of decreased gas absorption capacity due to increased viscosity of the ionic liquid material caused by accumulation of CO2 adsorption products can be avoided;

[0037] Therefore, the modified guanidine ionic liquid / mesoporous carbon composite fiber material of the present invention has large CO2 absorption capacity, good thermal stability and recyclability, and can achieve efficient capture of CO2 in industrial exhaust gas and reduce the cost of removing CO2 from industrial tail gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a schematic diagram of the preparation of modified guanidine ionic liquid / mesoporous carbon composite fiber materials. DETAILED DESCRIPTION

[0039] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention or the technical solutions in the prior art will be clearly and completely introduced below. Obviously, the embodiments described below are only some implementation methods of the present invention, rather than all embodiments.

[0040] Embodiment 1:

[0041] Experimental group 1-1

[0042] In this experimental group, Toyo Tanso Cnovel with a specific surface area of ​​1200m2 / g and a pore size of 5nm was selected. TM MH-18-PT50 mesoporous carbon material; hexadecyltrimethylammonium bromide (CTAB) was selected to modify the carbon carrier, wherein the mass ratio of CTAB to the mesoporous carbon material was 5%; 1-methylpiperidine and 1,6-dibromohexane were selected for guanidine ionic liquid cation modification, wherein the volume ratio of 1-methylpiperidine to 1,6-dibromohexane was 1:3, and the molar ratio of the product after the reaction to 1,1,3,3-tetramethylguanidine was 1:2; lysine was selected for guanidine ionic liquid anion modification, wherein the molar ratio of lysine to cation-modified guanidine ions was 1:1. The mass ratio of modified guanidine ionic liquid: modified mesoporous carbon: polyacrylic acid (PAA) in the modified guanidine ionic liquid / mesoporous carbon composite fiber material was 5:4:1.

[0043] S1. Dissolve cetyltrimethylammonium bromide (CTAB) in an organic solvent to form a stable mixed solution. TM The mesoporous carbon was added to the mixed solution and mechanically stirred for 24 hours, wherein the mass ratio of CTAB to the mesoporous carbon material was 5%. After the reaction was completed, the excess reaction product was ultrasonically washed away with anhydrous ethanol and ultrapure water, and filtered with a PTFE filter membrane, and the filtered mesoporous carbon was vacuum dried at 60°C for 24 hours to obtain the modified mesoporous carbon.

[0044] S2. Dissolve 1-methylpiperidine in ethyl acetate (volume ratio of 1-methylpiperidine to ethyl acetate is 1:2) to prepare a solution; then dissolve 1,6-dibromohexane in ethyl acetate (volume ratio of 1,6-dibromohexane to ethyl acetate is 1:2) to prepare a solution. Then drip the bromohexane solution dropwise into the 1-methylpiperidine solution, react at 40°C for 24 hours, and then filter to obtain a solid. After repeatedly washing with ethyl acetate, vacuum dry at 80°C for 24 hours to form the product 1-bromohexane-piperidine.

[0045] S3, 1,1,3,3-tetramethylguanidine, 1-bromohexane-piperidine and anhydrous potassium carbonate were dissolved in acetonitrile, and refluxed and stirred for 24 hours at a temperature of 60°C, wherein the molar ratio of 1,1,3,3-tetramethylguanidine, 1-bromohexane-piperidine and anhydrous potassium carbonate was 1:2:3. Then, the mixture was cooled and filtered, H2O (the volume ratio of acetonitrile to water was 1:1) was added to the filtrate, and the mixture was washed with petroleum ether, and then the petroleum ether phase was extracted with water. The two aqueous phases were combined, and the above solution was extracted with dichloromethane, anhydrous sodium sulfate was added to remove water, and dichloromethane was removed by rotary evaporation to obtain a guanidine ion product after cationic modification.

[0046] S4, dissolving lysine in water, adding the guanidine ion intermediate under vigorous stirring, wherein the molar ratio of lysine to the guanidine ion intermediate is 1:1-2. Then, after mixing and stirring at room temperature for 48 hours, the mixture is evaporated under reduced pressure at 55° C. Finally, the mixture is vacuum dried at 55° C. for 48 hours to constant weight, thereby obtaining anion-modified guanidine ionic liquid.

[0047] S5. Add CTAB-modified mesoporous carbon to the solvent (isopropanol, ultrapure water), then add polyacrylic acid (PAA) spinning solution, and after high-speed homogenization, add tetramethylguanidine ionic liquid modified by anions and cations to form a mixed spinning solution, in which the mass ratio of modified guanidine ionic liquid: modified mesoporous carbon: polyacrylic acid (PAA) is 5:4:1. Then, add it to the electrospinning device for electrospinning to obtain modified guanidine ionic liquid / mesoporous carbon composite fiber material. Among them, the electrospinning conditions are: static voltage is 40kV, injection pump flow rate is 2mL / h, and the distance between the spinneret and the receiving screen is 15cm.

[0048] Experimental Group 1-2

[0049] This experimental group refers to the method for preparing modified guanidine ionic liquid / mesoporous carbon composite fiber material provided by experimental group 1-1. The difference between this experimental group and experimental group 1-1 is that in S1, the mass ratio of CTAB to mesoporous carbon material is 1%. The rest of the raw material ratio and preparation method are strictly consistent with those of experimental group 1-1.

[0050] Embodiment 2:

[0051] Experimental Group 2-1

[0052] This experimental group refers to the method for preparing modified guanidine ionic liquid / mesoporous carbon composite fiber material provided by experimental group 1-1. The difference between this experimental group and experimental group 1-1 is that in S3, the molar ratio of the product after the reaction to 1,1,3,3-tetramethylguanidine is adjusted to 1:4. The rest of the raw material ratios and preparation methods are strictly consistent with those of experimental group 1-1.

[0053] Experimental group 2-2

[0054] This experimental group refers to the method for preparing modified guanidine ionic liquid / mesoporous carbon composite fiber material provided by experimental group 1-1. The difference between this experimental group and experimental group 1-1 is that in S2, the volume ratio of 1-methylpiperidine to 1,6-dibromohexane is adjusted to 1:5. The rest of the raw material ratios and preparation methods are strictly consistent with those of experimental group 1-1.

[0055] Embodiment 3:

[0056] This experimental group refers to the method for preparing modified guanidine ionic liquid / mesoporous carbon composite fiber material provided by experimental group 1-1. The difference between this experimental group and experimental group 1-1 is that in S4, the molar ratio of lysine to cationic modified guanidine ions is adjusted to 1:2. The rest of the raw material ratios and preparation methods are strictly consistent with those of experimental group 1-1.

[0057] Embodiment 4:

[0058] This experimental group refers to the method for preparing modified guanidine ionic liquid / mesoporous carbon composite fiber materials provided by experimental group 1-1. The difference between this experimental group and experimental group 1-1 is that in S5, the mass ratio of modified guanidine ionic liquid: modified mesoporous carbon: polyacrylic acid (PAA) is adjusted to 16:4:1. The rest of the raw material ratios and preparation methods are strictly consistent with those of experimental group 1-1.

[0059] Comparative Example:

[0060] Control group 1

[0061] This experimental group directly selected the unmodified commercially available guanidine ionic liquid: 1,1,3,3-tetramethylguanidine.

[0062] Control group 2

[0063] This experimental group refers to the method for preparing modified guanidine ionic liquid / mesoporous carbon composite fiber materials provided by experimental group 1-1. The difference between this experimental group and experimental group 1-1 is that in S1, a CABOT Vulcan XC-72 carbon material with a specific surface area of ​​100m2 / g is selected. The rest of the raw material ratios and preparation methods are strictly consistent with those of experimental group 1-1.

[0064] Control group 3

[0065] This experimental group refers to the method for preparing fiber materials provided by experimental group 1-1. The difference between this experimental group and experimental group 1-1 is that the S2, S3, and S4 process steps are not carried out in the preparation, and the guanidine ionic liquid is not subjected to anion and cation modification treatment. The rest of the raw material ratios and preparation methods are strictly consistent with those of experimental group 1-1.

[0066] Control group 4

[0067] This experimental group refers to the method for preparing modified guanidine ionic liquid / mesoporous carbon composite fiber materials provided by experimental group 1-1. The difference between this experimental group and experimental group 1-1 is that the S2 and S3 process steps are not carried out in the preparation, and the guanidine ionic liquid is not subjected to cationic modification. The rest of the raw material ratios and preparation methods are strictly consistent with those of experimental group 1-1. The rest of the raw material ratios and preparation methods are strictly consistent with those of experimental group 1-1.

[0068] Control group 5

[0069] This experimental group refers to the method for preparing modified guanidine ionic liquid / mesoporous carbon composite fiber materials provided by experimental group 1-1. The difference between this experimental group and experimental group 1-1 is that the S4 process step is not carried out in the preparation, and the guanidine ionic liquid is not anion-modified. The rest of the raw material ratios and preparation methods are strictly consistent with those of experimental group 1-1. The rest of the raw material ratios and preparation methods are strictly consistent with those of experimental group 1-1.

[0070] Test items and test methods:

[0071] CO2 adsorption performance test: In order to examine the decarbonization effect of the modified guanidine ionic liquid on CO2 in industrial exhaust gas, the experimental conditions were operated for 60 minutes under normal pressure, temperature 40°C, and flue gas flow rate of 80mL / min, and the molar amount of CO2 adsorbed per mole of modified guanidine ionic liquid / mesoporous carbon composite fiber material-adsorbent was determined.

[0072] The test data in the test example of the present invention are shown in Table 1.

[0073] Table 1 Case test data

[0074]

[0075] Result analysis:

[0076] From the test results shown in Table 1, it can be seen that compared with the control group, the modified guanidine ionic liquid / mesoporous carbon composite fiber materials prepared in Examples 1 to 3 have a higher CO2 adsorption capacity.

[0077] Compared with Example 1-4, the modified guanidine ionic liquid / mesoporous carbon composite fiber material prepared in Experimental Group 1-1 has a higher adsorption capacity, indicating that Experimental Group 1-1 is the best process scheme of the present invention.

[0078] Comparing the composite materials provided by the experimental group 1-1 with those provided by the control group 1, it can be seen that the commercially available guanidine ionic liquids in the present invention have poor CO2 adsorption capacity without modification treatment and spinning treatment.

[0079] Comparing the composite materials provided by the experimental group 1-1 with those provided by the control group 2, it is possible to use a carbon material with a low specific surface area and no mesoporous structure in the present invention, and the CO2 adsorption capacity of the composite fiber material is poor.

[0080] Comparing the composite materials provided by the experimental group 1-1 with those provided by the control group 3, it can be seen that after the guanidine ionic liquid in the present invention is modified by anions and cations, the CO2 adsorption capacity of the composite fiber material is significantly increased.

[0081] Comparing the composite materials provided by the experimental group 1-1 with those provided by the control groups 4 and 5, it can be seen that after the guanidine ionic liquid in the present invention is modified by anions and cations, the CO2 adsorption capacity of the composite fiber material is increased, and the performance is more excellent after anion modification.

[0082] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture, characterized in that: The composite fiber material mainly includes a CO2 fiber adsorbent layer composed of hexadecyltrimethylammonium bromide modified mesoporous carbon material, 1-bromohexane-piperidine and lysine modified guanidine ionic liquid, and polyacrylic acid (PAA) material, wherein the fiber diameter of the modified guanidine ionic liquid / mesoporous carbon composite fiber material is 200-500nm.

2. The mesoporous carbon material in the modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture according to claim 1, characterized in that: Hexadecyltrimethylammonium bromide modified mesoporous carbon materials.

3. The mesoporous carbon material in the modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture according to claim 2, characterized in that: The specific surface area of ​​the mesoporous carbon is 800-1500m 2 / g, pore size 4-8nm, pores are through holes.

4. The modified mesoporous carbon material in the modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture according to claim 2, characterized in that: The material for modifying the mesoporous carbon is a long-chain alkyl molecule such as hexadecyltrimethylammonium bromide.

5. The ionic liquid in the modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture according to claim 1 is a modified guanidine ionic liquid, characterized in that: The mass ratio of hexadecyltrimethylammonium bromide to the mesoporous carbon material is 1-10%.

6. The ionic liquid in the modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture according to claim 1 is a modified guanidine ionic liquid, characterized in that: Guanidine ionic liquids modified with 1-bromohexane-piperidine and lysine.

7. The modified ionic liquid of the modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture according to claim 6, characterized in that: The ionic liquid is 1,1,3,3-tetramethylguanidine and its derivatives.

8. The modified ionic liquid of the modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture according to claim 6, characterized in that: 1-bromohexane-1-piperidine is selected for cation modification of guanidine ionic liquid. The material structure of the cation-modified guanidine ionic liquid is as follows:

9. The modified ionic liquid of the modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture according to claim 6, characterized in that: Lysine is used in guanidine ionic liquids to modify the anions of guanidine ionic liquids. The material structure of the modified guanidine ionic liquids is as follows:

10. A method for preparing a modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture, the preparation method comprising: S1. Dissolve cetyltrimethylammonium bromide (CTAB) in an organic solvent to form a stable mixed solution. TM The mesoporous carbon was added to the mixed solution and mechanically stirred for 24 hours. After the reaction was completed, the excess reaction product was ultrasonically washed away with anhydrous ethanol and ultrapure water, filtered with a PTFE filter membrane, and the filtered mesoporous carbon was vacuum dried at 60°C for 24 hours to obtain the modified mesoporous carbon. S2, dissolving 1-methylpiperidine in ethyl acetate to prepare a solution; then dissolving 1,6-dibromohexane in ethyl acetate to prepare a solution. Then drip the bromohexane solution dropwise into the 1-methylpiperidine solution, react at 40°C-60°C for 24 hours, and then filter to obtain a white solid, wash the white solid repeatedly with ethyl acetate for 3 times, and then vacuum dry at 80°C for 24 hours to form an intermediate product 1-bromohexane-1-piperidine, wherein the volume ratio of 1-methylpiperidine to 1,6-dibromohexane is 1:2-5. S3. Add 1,1,3,3-tetramethylguanidine, 1-bromohexane-1-piperidine and anhydrous potassium carbonate to acetonitrile, reflux and stir at 60°C for 24 hours, wherein the molar ratio of 1,1,3,3-tetramethylguanidine to 1-bromohexane-1-piperidine is 1:2-3. Cool and filter, add H2O to the filtrate, wash with petroleum ether, and then extract the petroleum ether phase with water. The two aqueous phases are combined, and then the above solution is extracted with dichloromethane several times, anhydrous sodium sulfate is added to remove water, and dichloromethane is removed by rotary evaporation to obtain a guanidine ion intermediate. S4, dissolving lysine in water, adding the guanidine ion intermediate under vigorous stirring, wherein the molar ratio of lysine to the guanidine ion intermediate is 1:1-2. Then, after mixing and stirring at room temperature for 48 hours, the mixture is evaporated under reduced pressure at 55° C. Finally, vacuum drying is performed at 55° C. for 48 hours to constant weight, thereby obtaining the prepared ionic liquid—amino tetramethylguanidine. S5, adding CTAB modified mesoporous carbon to a solvent (isopropanol, ultrapure water), then adding polyacrylic acid (PAA) spinning solution, after high-speed homogenization, adding amino tetramethylguanidine ionic liquid to form a mixed spinning solution. Then, adding it to an electrospinning device, electrospinning is performed to obtain a modified guanidine ionic liquid / mesoporous carbon composite fiber material.

11. The method for preparing a modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture according to claim 10, characterized in that: In S2 and S3, the volume ratio of 1-methylpiperidine to 1,6-dibromohexane is 1:2-5; the molar ratio of the product 1-bromohexane-piperidine to 1,1,3,3-tetramethylguanidine is 4-2:

1.

12. A method for preparing a modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture according to claim 10: in S4, the molar ratio of lysine to the guanidine ion intermediate is 1:1-2.

13. According to claim 10, a method for preparing a modified guanidine ionic liquid / mesoporous carbon composite fiber material for CO2 capture: in S5, the mass ratios of modified guanidine ionic liquid: modified mesoporous carbon: polyacrylic acid (PAA) in the modified guanidine ionic liquid / mesoporous carbon composite fiber material are 100-50:40-20:10-5 respectively.